sum rule

The sum rule states that



See the proof of the sum rule (


ddx(x+1) = ddxx+ddx1=1
ddx(x2-3x+2) = ddxx2+ddx(-3x)+ddx(2)=2x-3
ddx(sinx+cosx) = ddxsinx+ddxcosx=cosx-sinx
Title sum rule
Canonical name SumRule
Date of creation 2013-03-22 12:28:09
Last modified on 2013-03-22 12:28:09
Owner mathcam (2727)
Last modified by mathcam (2727)
Numerical id 8
Author mathcam (2727)
Entry type Theorem
Classification msc 26A24
Related topic Derivative
Related topic ProductRule
Related topic FixedPointsOfNormalFunctions